Islamic Legal Analysis of Pregnancy Delay in the Ruwatan Tradition: A Perspective from Nahdlatul Ulama Scholars in Kebun Jeruk, West Lampung - Ruli Fajri (CV. FOUNDAE, 2025)
The Javanese are one of the ethnocultural groups in Indonesia known for their rich local traditions, one of which is the ruwatan ritual. In some Javanese communities, ruwatan is practiced as a pre-pregnancy ritual, which leads to the phenomenon of pregnancy delay. This phenomenon presents an interesting issue for study, particularly from the perspective of Islamic law, specifically the views of the scholars of Nahdlatul Ulama (NU). This study aims to analyze the legal status of pregnancy delay during the ruwatan ritual based on fiqh studies and the concept of ‘urf. The research employs a qualitative descriptive-analytical approach, utilizing in-depth interviews with leaders of the MWCNU Kebun Tebu and participatory observation in Pujaya 1 Village, West Lampung. Data are analyzed thematically using the approach of usul al-fiqh. The findings of this study indicate that pregnancy delay during ruwatan is generally based on the weton calculation or occurs on the 1st of suro. According to the MWCNU Kebun Tebu’s perspective, this practice is considered makruh if not motivated by emergency (medical) reasons, but it is still regarded as a valid ‘urf (‘urf sahih) because it serves a positive purpose, such as household adaptation, along with spiritual dimensions like dhikr (remembrance of God) and prayers. Thus, although the delay of pregnancy in the context of ruwatan is viewed as makruh from an Islamic legal perspective, this tradition remains acceptable as long as it does not conflict with Islamic law and contains elements of maslahah (public benefit) for the couple.